Photolysis of n-propyl formate in the presence of O2 and NO2: Peroxy formyl propyl nitrate CH3CH2CH2OC(O)OONO2 synthesis and characterization - Vila, Jesús Alberto (2015)
The photo-oxidation of n-propyl formate (initiated by chlorine atoms) was studied in the presence of NO2, and the products were identified. The Cl atom attack to the molecule occurs in four sites, leading to the formation of formic acid, carbon dioxide, dicarbonylic products, nitrates, peroxy propionyl nitrate (CH3CH2C(O)OONO2, PPN), and a new peroxynitrate, peroxy formyl propyl nitrate (CH3CH2CH2OC(O)OONO2, PFPN). To characterize bulk quantities of the PFPN, its synthesis was carried out by the photolysis of mixtures of CH3CH2CH2OC(O)H, NO2, Cl2, and O2. After purification, its infrared spectrum and thermal stability were determined. The main infrared absorption bands and their corresponding cross sections are 796, 1219, 1302, 1741, and 1831 cm–1 (1.16, 3.11, 0.88, 2.42, and 1.34 × 10–18 cm2 molec–1, respectively). Thermal decomposition was studied as a function of pressure from 6.0 to 1000 mbar at 298 K, and the activation energy was determined between 293 and 304 K at total pressures of 9.0 and 1000 mbar (Ea = 98 ± 3 and 110 ± 2 kJ/mol, respectively). The atmospheric thermal lifetimes were obtained from kinetic parameters.